Sialyllactose and Galactooligosaccharides Promote Epithelial Barrier Functioning and Distinctly Modulate Microbiota Composition and Short Chain Fatty Acid Production In Vitro - Perdijk, Olaf; van Baarlen, Peter; Fernandez-Gutierrez, Marcela M.; van den Brink, Erik; Schuren, Frank H. J.; Brugman, Sylvia; Savelkoul, Huub F. J.; Kleerebezem, Michiel; van Neerven, R. J. Joost (Frontiers in Immunology, 2019)
Human milk oligosaccharides (HMO) and prebiotic oligosaccharides are proposed to confer several health benefits to the infant. They shape the microbiota, have anti-inflammatory properties, and support epithelial barrier functioning. However, in order to select the best oligosaccharides for inclusion in infant formulas, there is a need to increase our understanding of the specific effects of HMO and prebiotics on the host immune system. Therefore, we investigated the effects of the HMO sialyllactose (SL), and galactooligosaccharides (GOS) on epithelial barrier functioning, microbiota composition, and SCFA production. Transcriptome analysis showed that SL and GOS both induced pathways that regulate cell cycle control in fully polarized Caco-2 cells. This gene-expression profile translated to a phenotype of halted proliferation and included the induction of alkaline phosphatase activity, a marker of epithelial cell differentiation. SL and GOS also promoted re-epithelialization in an in vitro epithelial wound repair assay. SL induced the outgrowth of members of the Bacteroides genus, including B. fragilis as well as Feacalibacterium prausnitzii, and led to elevated levels of propionate and butyrate production. Interestingly, these microbial species have both been associated with protection against colitis in animal models. GOS appeared to specifically support the outgrowth of the Bifidobacterium genus, which coincided with elevated levels of lactate and butyrate production. Our results show that SL and GOS can both modulate epithelial barrier function by inducing differentiation and epithelial wound repair, but differentially promote the growth of specific genera in the microbiota, which is associated with differential changes in SCFA profiles.